(3cfR GdObGFb aj aQhY GdMfajIs - (3GdnqfnSaj, CHh GdHQcGJ, MGaX GdOjf, YHO Gddg Hf CMeO Hf eMehO, (B710 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CYR GdYde aj GdCYUGQ hCYdG MRHg aj GdCeUGQ deG QCjJ Gdgee eGFdI Edi GdeNJUQGJ hGdWHGY QGZHI Yf GdeWhdGJ CQOJ Gf CdNU GdhGaj HPcQ eG Ye hbhYg hcKQ hLhOg s
(3BNQgG (B:s
(3hfOH dHS GdShGO hEQSGd PfH GdYeGeI Hjf cJajg Edi hSW GdXgQ hddTGH GdYGde Cf jJbOe Ydi GdTjN GdLGgd hGdMGaX GdbQBf Cf jNJe aj CQHYjf jheGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 67s
(3eYLe GdeDdajf (B2 / 228s
(3cTa GdXfhf (B2 / 1515s
(3gOjI GdYGQajf (B1 / 464s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs